Čoarvemátta - Terrängmodell - (:unkn) unknown (Chalmers tekniska högskola // Institutionen för arkitektur och samhällsbyggnadsteknik, 2025)
Čoarvemátta comes from the Sámi words for horn and root, after the innermost and strongest part of the reindeer antlers. This symbolizes different qualities and strengths and represents elements that unite, as Čoarvemátta will be a unifying force for the institutions that share the building: the Sami National Theatre Beaivváš and the Sami High School and Reindeer Herding School. The landscape model’s purpose is to show the placement of the building, both in relation to the built-up area of Kautokeino and to the vast plateau, which is reindeer herding lands. The small sliver format was chosen to highlight this relationship. The placement of the building is interesting, as the idea of a monumental, cultural building placed in such a non-urban way is unusual.
Čoarvemátta - Terrain model
Keywords: Sami